2017
DOI: 10.18632/oncotarget.19892
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of the T cell receptor β repertoire reveals signature patterns and clonal drift in atherosclerotic plaques and patients

Abstract: The T cell receptor (TCR) β repertoire directly reflects the status of T cell function. Meanwhile, the immune/inflammatory responses regulated by T cells are the critical determinants of atherosclerosis development. However, due to technical limitations, the composition and molecular characteristics of the TCR repertoire in atherosclerotic patients have not been fully elucidated. In the present study, we use powerful immune repertoire sequencing technology to study this issue. Results show that the utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
1
13
0
2
Order By: Relevance
“…This protection was associated with increased IL-10 production, an anti-inflammatory cytokine mainly secreted by regulatory T cells (Tregs). In atherosclerotic patients, an oligoclonal T cell repertoire was observed in comparison to healthy patients [91,92]. This observation further supports the relevance of antigen presentation during disease development.…”
Section: Macrophagessupporting
confidence: 74%
“…This protection was associated with increased IL-10 production, an anti-inflammatory cytokine mainly secreted by regulatory T cells (Tregs). In atherosclerotic patients, an oligoclonal T cell repertoire was observed in comparison to healthy patients [91,92]. This observation further supports the relevance of antigen presentation during disease development.…”
Section: Macrophagessupporting
confidence: 74%
“…In addition, T-helper cells show an increasing maturation into antigenexperienced effector/memory (T EM ) and central-memory (T CM ) T cells in the lymph nodes ( Figure 1a) that is also observed in atherosclerotic plaques 28,31 . Sequencing of the TCR revealed an oligoclonal origin of lesional T cells 32,33 suggesting that some (antigenspecific) T cell clones actively expand in the plaque. The enhanced activation of T cells is accompanied by an expansion of lymph nodes draining the atherosclerotic aorta in aged atherosclerotic Apoe −/− mice ( Figure 1b) and a local and systemic pro-inflammatory response that is further enhanced by a hypercholesterolemia-inducing diet [34][35][36] .…”
Section: Evidence For An Autoimmune Response In Atherosclerosismentioning
confidence: 99%
“…Diversified TCRs were required for an intense adaptive immune responses, while pressures from both internal and external help shape the diversity of TCR [33,34]. The TCR repertoire of patients with atherosclerosis has been investigated and level of diversity was reduced in AS plaques [35]. In the present study, we found that clonal diversity of the TCR CDR3 β decreased in ACS patients as compared to NCA.…”
Section: Discussionmentioning
confidence: 47%